Distribution-led growth through methodological lenses - Michalis Nikiforos (Levy Economics Institute of Bard College, 2016)
This paper presents a methodological discussion of two recent 'endogeneity' critiques of the Kaleckian model and the concept of distribution-led growth. From a neo-Keynesian perspective, and following Kaldor (1955) and Robinson (1956), the model is criticized because it treats distribution as quasi-exogenous, while in Skott (2016) distribution is viewed as endogenously determined by a series of (exogenous) institutional factors and social norms, and therefore one should focus on these instead of the functional distribution of income per se. The paper discusses how abstraction is used in science and economics, and employs the criteria proposed by Lawson (1989) for what constitutes an appropriate abstraction. Based on this discussion, it concludes that the criticisms are not valid, although the issues raised by Skott provide some interesting directions for future work within the Kaleckian framework.
Keywords: B22; B41; B50; E11; E12; 330; Kaleckian Model; Distribution-led Growth; Abstraction